2016
DOI: 10.1177/1708538116673018
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to secondhand smoke and risk of peripheral arterial disease in southern Chinese non-smokers: The Guangzhou Biobank Cohort Study-Cardiovascular Disease Sub-cohort

Abstract: Objectives We studied the association between secondhand smoke (SHS) exposure and peripheral arterial disease (PAD) in Chinese non-smokers. Methods We conducted a cross-sectional study using baseline data from the Guangzhou Biobank Cohort Study: Cardiovascular Disease Sub-cohort Study (GBCS-CVD). Guangzhou residents aged ≥ 50 years were recruited between 2003 and 2008. Baseline data included measurement of ankle brachial pressure index (ABPI) and self-reported smoking status and SHS exposure. Univariate and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Even limited levels of SHS exposure are associated with 25-30% increased CVD risk [4][5][6]. Compared to non-exposed never smokers and following adjustment for potential confounding factors, middle-aged never smokers with ≥25 h/week SHS exposure at home displayed 7.86 fold elevated risk of peripheral arterial disease [31]. A recent meta-analyses conducted among 23 prospective and 17 case-control studies revealed that the pooled relative risk (RR) for CVD (n=38 studies) in never smokers exposed to SHS, as compared to their nonexposed counterparts, is 1.23 (95% CI: 1.16-1.31) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Even limited levels of SHS exposure are associated with 25-30% increased CVD risk [4][5][6]. Compared to non-exposed never smokers and following adjustment for potential confounding factors, middle-aged never smokers with ≥25 h/week SHS exposure at home displayed 7.86 fold elevated risk of peripheral arterial disease [31]. A recent meta-analyses conducted among 23 prospective and 17 case-control studies revealed that the pooled relative risk (RR) for CVD (n=38 studies) in never smokers exposed to SHS, as compared to their nonexposed counterparts, is 1.23 (95% CI: 1.16-1.31) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking has been implicated as a risk factor for ocular diseases such as age-related macular degeneration 30,31 and retinal vein occlusion. 32 It is also a known risk factor for stroke, 33 cardiovascular diseases, 34,35 and peripheral vascular diseases. 36 Based on the present study, the ex-smoker and active smoker groups were not found to be significantly associated with PACG.…”
Section: Discussionmentioning
confidence: 99%